(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This proposition acknowledged education, artistic process, and inspirations based on the explored medium, focusing on the concept and contextual analysis of Zarina Hashmi’s works. As Zarina Hashmi had always been interested in space and its adventures, her minimalist artwork draws inspiration from Urdu poetry. Although Zarina's works give the impression that this language hides in a blank and that frames conceal themselves beneath lines and boundaries. The most recognizable geometry was created on the surface of cast paper sculptures, drawings, and prints; the simple, dramatic, and enigmatic outcomes were more aesthetically expressed. This research paper is centered on the development of visual art, qualitative analysis, and empirical art practices. Her work questions the boundaries, delimitations, and navigation of familiar spaces like "country" and "home," as well as the emotions and memories that evoke enduring imprints in the minds of viewers. Given her extensive artistic path, it is astonishing that she navigated from the personal to the universal.